2011
DOI: 10.1111/j.1468-0475.2011.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

When a Precedent of Donation Favors Defection in the Prisoner’s Dilemma

Abstract: In this paper, we examine the question of whether a collective activity can influence cooperation in a subsequent repeated one-shot prisoner's dilemma ( PD) game. We conduct two series of experiments. The first consists of control experiments in which 30 periods of a PD game are played, with a random rematching of the pairs in every period. In a second series of experiments, subjects first play a donation game (DG) and then the PD game. In the DG, they collectively discuss the amount of a donation to a given c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…As discussed earlier, Garapin et al (2011) suggest that prior instances of generosity may result in lower levels of generosity at a later date, suggesting a lower frequency of cooperation in the hotfirst condition than the cold-first condition. However, Axelrod and Hamilton's (1981) research suggests the opposite effect.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As discussed earlier, Garapin et al (2011) suggest that prior instances of generosity may result in lower levels of generosity at a later date, suggesting a lower frequency of cooperation in the hotfirst condition than the cold-first condition. However, Axelrod and Hamilton's (1981) research suggests the opposite effect.…”
Section: Discussionmentioning
confidence: 87%
“…Garapin, Llerena and Michel (2011) found that when participants play a game of Prisoner's Dilemma, after playing a donation game, they were less likely to cooperate. This suggests that prior instances of generosity may result in lower levels of generosity at a later date, which may have a significant effect on a repeated measures design.…”
Section: Temperature Priming and Cooperationmentioning
confidence: 99%
“…In similar fashion, Garapin, Llerena, and Hollard (2010) reports that the average rate of cooperation from four sessions of the game ranged from 15.4% to 29.7% (Table 3). However, Vlaev and Chater (2007) find that the percentage of cooperative games in three different payoff setting are up to 33%, 50%, and 71%.…”
Section: The Prisoner's Dilemma Gamementioning
confidence: 69%
“…The proportion of cooperative strategy is relatively low compared to that of previous experiments such as Bereby-Meyer and Roth (2006) and Garapin, Llerena, and Hollard (2010). Their experiments ended with cooperative rate at least 15% and in one session it was close to 30%.…”
Section: A General Reviewmentioning
confidence: 91%
See 1 more Smart Citation